2011
DOI: 10.5194/acp-11-12007-2011
|View full text |Cite
|
Sign up to set email alerts
|

Primary versus secondary contributions to particle number concentrations in the European boundary layer

Abstract: Abstract.It is important to understand the relative contribution of primary and secondary particles to regional and global aerosol so that models can attribute aerosol radiative forcing to different sources. In large-scale models, there is considerable uncertainty associated with treatments of particle formation (nucleation) in the boundary layer (BL) and in the size distribution of emitted primary particles, leading to uncertainties in predicted cloud condensation nucleiCorrespondence to: C. L. Reddington (c.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
118
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 112 publications
(130 citation statements)
references
References 110 publications
(176 reference statements)
12
118
0
Order By: Relevance
“…The global annual production of SOA from these yield experiments is detailed in Table 2 and all lie within the wide range of previous estimates (Griffin et al, 1999;Kanakidou et al, 2005;Goldstein and Galbally, 2007;Heald et al, 2010Heald et al, , 2011Spracklen et al, 2011b). In GLOMAP, the simulated aerosol size distributions, and therefore the CCN concentrations, are sensitive to the treatment of primary anthropogenic emissions (Reddington et al, 2011;Spracklen et al, 2011a), in particular the emission characteristics of primary carbonaceous aerosol. Here, we emit primary carbonaceous particles with the distribution characteristics described by Stier et al (2005) in our standard simulations, i.e.…”
Section: Model Experimentsmentioning
confidence: 60%
See 1 more Smart Citation
“…The global annual production of SOA from these yield experiments is detailed in Table 2 and all lie within the wide range of previous estimates (Griffin et al, 1999;Kanakidou et al, 2005;Goldstein and Galbally, 2007;Heald et al, 2010Heald et al, , 2011Spracklen et al, 2011b). In GLOMAP, the simulated aerosol size distributions, and therefore the CCN concentrations, are sensitive to the treatment of primary anthropogenic emissions (Reddington et al, 2011;Spracklen et al, 2011a), in particular the emission characteristics of primary carbonaceous aerosol. Here, we emit primary carbonaceous particles with the distribution characteristics described by Stier et al (2005) in our standard simulations, i.e.…”
Section: Model Experimentsmentioning
confidence: 60%
“…The treatment of primary carbonaceous emissions has been shown to strongly influence particle number concentrations and aerosol size distributions simulated by global aerosol microphysics models (Reddington et al, 2011;Spracklen et al, 2011a). We therefore compared against measurements filtered to minimise the influence of these particles: that is, data for terrestrial locations with a simulated present-day / pre-industrial CCN concentration ratio (calculated from [CCN] expt.…”
Section: Pearson Correlation Coefficient (R)mentioning
confidence: 99%
“…The overall kappa-variability will be inferred and discussed in context with the effective average kappa of 0.3 ± 0.1 and 0.7 ± 0.2 as estimated by Andreae and Rosenfeld (2008) for the continental and marine background aerosol, respectively. The former value has recently been superseded by 0.3 ± 0.2 which seems still fairly well constrained with regard to cloud droplet formation (Reutter et al, 2009;Pawlowska, 2010, 2011). Kappa deduced from the CCN data (i.e.…”
Section: Ccn Formation and Cloud Droplet Activationmentioning
confidence: 99%
“…GLOMAP predictions of particle number over Europe were compared to aircraft and ground-based measurements recorded during the May 2008 EUCAARI intensive campaign and Long Range Experiment (LONGREX) by Reddington et al (2011). It was found that the spatial distributions of campaign-mean number concentrations >50 nm (N 50 ) and >100 nm (N 100 ) dry diameter were well captured by the model (R 2 >0.8) and the normalised mean bias was also small (−18 % for N 50 and 1 % for N 100 ) if a small emission size was assumed for primary carbonaceous particles, as used by AEROCOM .…”
Section: Global Particle Number Concentrations With Glomapmentioning
confidence: 99%
“…Adding to the database of observations helps constrain the uncertainties associated with aerosol size. Thus, to improve BB-aerosol-climate interactions in models, there is a need to characterize the size of particles in aging and aged biomass-burning plumes for a range of fire types and atmospheric conditions (Bauer et al, 2010;Chen et al, 2010;Lee et al, 2013;Pierce et al, 2007;Reddington et al, 2011;Spracklen et al, 2011). In this paper, we specifically investigate the size distributions measured in aged plumes (1-2 days) of large boreal forest fires over Canada.…”
Section: Biomass-burning Particlesmentioning
confidence: 99%